Fire Regime in a Peatland Restoration Area: Lesson from Central Kalimantan - Bekti Larasati; Mamoru Kanzaki; Ris Hadi Purwanto; Ronggo Sadono (Jurnal Ilmu Kehutanan)
Peat fires have caused carbon emissions and damage to local and regional communities in Indonesia. An effective fire prevention system is required for mitigating climate change and enabling sustainable development of peatlands. This study examined the fire regime in a peatland restoration area in Central Kalimantan in order to assist the establishment of a fire prevention system. The fire regime was analysed using spatial-temporal analysis, land cover change mapping, and logistic regression analysis. Spatial-temporal analysis was done using monthly Niño 3.4 sea surface temperature anomalies, daily rainfall, and MODIS Active Fire (MCD14DL) hotspots from 2006 to 2015. Land cover change was mapped using Landsat imagery from2014, 2015 and 2016. Logistic regression analysis was conducted to identify significant factors that increase fire risk. The temporal analysis showed that the strongest El Niño occurred in 2015, when the region experienced a 140-days drought period. The highest number of hotspots was also observed in this year, with hotspots concentrated in the latter half of drought period. Moreover, spatial analysis using Kernel Density Estimation (KDE) showed fire recur in degraded areas. The logistic regression analysis used topographic and proximity factors, land cover classes, and soil types as independent variables. It showed that fire in 2014 and 2015 was associated with several land cover classes and was related to historical fire occurrence areas based on KDE results. Several area of peatland forests burned in 2015 and occurred at the forest edge areas located near cultivated or degraded land (e.g. shrubland) and oil palm plantations. Based on the results, the fire regime in the study area is characterized by fires that occurring/recurring in relation to climatic conditions, especially drought periods, and are typically located in cultivated or degraded land cover classes. These parameters should be considered in developing a fire prevention system in the restoration area.